Developpe et reduis chaque expression :

D= 3 x (x+5)
E= 3x x (-4+x)
F= 3(b-4)
G= -4 (7+u)
H= -2 (5x-1)
I= -3a (6 - 5a)
J= (x+1) (x+5)
K= (4x+5) (2-3u)
L= (5u+1) (2-3u)
M= (-3+n) (-2n - 5)
N = 6+ (5y-2) (3-4y)
O = -3y (2+5y) -4 (1-2y) + (3y²-5y+3)
P= (x+5) (2x - 5) - (3x² - 7x + 5)

merci beaucoup

1

Réponses

2014-10-25T18:39:22+02:00
Bonsoir

D= 3 x (x+5) = 3x + 15 x (à moins que ton x soit la lettre)
E= 3x x (-4+x) = - 12 x+ 3 x²
F= 3(b-4) = 3b - 12
G= -4 (7+u) = - 28 - 4 u
H= -2 (5x-1) = - 10 x + 2
I= -3a (6 - 5a) = - 18 a + 15 a²

J= (x+1) (x+5) = x ² + 5 x + x +5 = x ² + 6x +5
K= (4x+5) (2-3u) = 8 x - 12 xu + 10 - 15 u 
L= (5u+1) (2-3u) = 10 u - 15 u² +2 - 3 u
M= (-3+n) (-2n - 5) = 6 n + 15 - 2 n - 5n = - n +15
N = 6+ (5y-2) (3-4y) = 6 + 15 y - 20 y² - 6 + 8 y = - 20 y² + 23 y 
O = -3y (2+5y) -4 (1-2y) + (3y²-5y+3) = - 6 v - 15 v² - 4 + 8 y + 3y² -5y +3 
= - 15 v² + 3y² + 3 y - 6 v - 1
P= (x+5) (2x - 5) - (3x² - 7x + 5) = 2 x² - 5 x + 10 x - 25 - 3 x² + 7x - 5 = - x² - 12 x - 30